"The Only Safe Guide is Love": Models of Engaging Luther's Ethical Hermeneutic for Theological Responses to the Affirmation of Same‐Sex Sexuality. (December 2013) - Cox, Jillian
Abstract Lutheran theological discussions over the morality of same‐sex sexuality not only raise "ethical" questions, but point to deeper interpretive tensions that arise when resources of the tradition are interpreted in new contexts. Responding to these debates, in this article I propose that Luther's application of the law to challenging ethical situations provides a historically situated hermeneutic that can redirect theological discussions on same‐sex sexuality. Drawing upon feminist Lutheran and queer theological work, I consider how we may reengage with Luther in a way that is both faithful to his commitments, and also takes queer people seriously as moral subjects.